E-Service Quality in Sustainable Digital Business: How it is influenced by Customer Perceived Culture - Koeswandi, Tika Annisa (Journal of Business Management Education (JBME), 2024)
This study aims to determine the influence of consumers' perceived culture and e-service quality on Netflix subscribers in Indonesia as a sustainable digital business. This research is quantitative descriptive research involving the object is Netflix. The population of this study is active Netflix users who have made at least 2 purchases/subscriptions. It is known that the number of Netflix subscribers in West Java is 850,000 users. However, it is not defined by the population framework. Thus, the purposive sampling method - non-probability as many as 100 people. The constant value (a) is 12,509, while the value of e-service quality (b / regression coefficient) is 0.321. So the constant 12,509 implies that the consistent value of the e-service quality variable is equal to 12,509. Meanwhile, the servicescape regression coefficient of 0.321 means that for every 1% addition to the value of customer-perceived culture, the value of e-service quality will increase by 0.321. The regression coefficient is considered positive, so it can be said that the direction of the influence of customer-perceived culture on e-service quality is also positive. So it can be concluded that the significance value is 0.000 0.05. Thus, customer-perceived culture affects e-service quality. From table 4.6, it can also be seen that the T-value is 3.227 T-table is 2.618. So, the variables affecting customer-perceived culture affect e-service quality. For further research, it is recommended to examine whether the impact on loyalty/enjoyment in using services from the cultural base is.